THE STYLISTIC ROLE OF DIALECTS IN M. SHOLOKHOV'S NOVEL "QUIET DON" (American Journal of Interdisciplinary Research and Development, 2024)
This analysis delves into the intricate use of dialects in M. Sholokhov's "Quiet Don," exploring how linguistic diversity enhances the novel's stylistic depth. The study examines the cultural and narrative implications of various dialects, emphasizing their role in character development, setting authenticity, and overall storytelling.